Recent developments in the facile bio-synthesis of gold nanoparticles (AuNPs) and their biomedical applications - Lee, Kar Xin; Shameli, Kamyar; Yew, Yen Pin; Teow, Sin Yeang *; Jahangirian, Hossein; Rafiee-Moghaddam, Roshanak; Webster, Thomas (Dove Medical Press, 2020)
Gold nanoparticles (AuNPs) are extensively studied nanoparticles (NPs) and are known to have profound applications in medicine. There are various methods to synthesize AuNPs which are generally categorized into two main types: chemical and physical synthesis. Continuous efforts have been devoted to search for other more environmental-friendly and economical large-scale methods, such as environmentally friendly biological methods known as green synthesis. Green synthesis is especially important to minimize the harmful chemical and toxic by-products during the conventional synthesis of AuNPs. Green materials such as plants, fungi, microorganisms, enzymes and biopolymers are currently used to synthesize various NPs. Biosynthesized AuNPs are generally safer for use in biomedical applications since they come from natural materials themselves. Multiple surface functionalities of AuNPs allow them to be more robust and flexible when combined with different biological assemblies or modifications for enhanced applications. This review focuses on recent developments of green synthesized AuNPs and discusses their numerous biomedical applications. Sources of green materials with successful examples and other key parameters that determine the functionalities of AuNPs are also discussed in this review.